Pengaruh Pemberian Bioherbisida Ekstrak Daun Ageratum conyzoides, Achasma walang, dan Wedelia trilobata terhadap Morfologi dan Stomata Daun Axonopus compressus - Riska Desi Aryani; Dian Palupi; Sri Lestari (Biotropic : The Journal of Tropical Biology, 2022)
Axonopus compressus (Sw.) Beauv. is a type of weeds that grows invasively and wildly. The weeds growth can be controlled by applying bioherbicides. The leaf extracts of Wedelia trilobata, Achasma walang, and Ageratum conyzoides produce allelochemicals that can be used as bioherbicides. The study aims to determine the effects of applying bioherbicides from the leaf extracts of W. trilobata, A. walang, and A. conyzoides on the morphology and stomata of A. compressus weeds. This study was done by: 1) making the leaf extracts W. trilobata, A. walang, and A. conyzoides with each concentration is 10 ppm, 25 ppm, and 50 ppm; 2) giving the leaf extracts treatment on the growth of A. compressus weeds; and 3) making observations on the morphology and stomata of A. compressus weeds. The results showed that there were morphological transformations on the A. compressus weeds after applying the bioherbicides. The transformations were seen in the changing color of the leaves, the reduced leaf size, and the increased number of chlorotic leaves. Meanwhile, the effects of applying the bioherbicides on the stomata of A. compressus weeds were also found, i.e. in the changing size of stomata, and the increased of stomatal index and density.